Pembuatan Video Animasi 2D Dengan Judul "Dampak Polusi Udara" Menggunakan Teknik Motion Tweening - Mitra Jayanti Pakan (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Air pollution is one of the most concerning environmental issues in the modern era. It is caused by various factors, including industrial activities, motor vehicles, and forest fires, which negatively affect environmental quality and public health. Limited public awareness of the impacts of air pollution highlights the need for educational media that is both informative and engaging. This study aims to design and develop a 2D animated video entitled "The Impact of Air Pollution" using the motion tweening technique as an educational medium to deliver information in an attractive and easily understandable way. The research employed the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The result of this study is a 2D animated video with a duration of 2 minutes and 53 seconds, published on YouTube. Evaluation involving 12 respondents yielded a positive score of 87.5%, indicating that the developed animation was considered engaging and easy to understand. Therefore, the 2D animated video developed using the motion tweening technique can serve as an effective educational medium for improving public awareness of the impacts of air pollution.